Microscopic Studies of Sedimentary Organic Matter: Key to Understanding Organic-Rich Strata, with Paleozoic Examples from Western Canada Basin - Stasiuk, L. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1999)
Summary Organic matter in sediments and sedimentary rocks provides data and interpretations on biosphere-geosphere interactions. In modern and ancient depositional settings, a combination of anoxia and substantial bio-productivity leads to the preservation of abundant organic matter, which in turn is transformed during subsequent burial into kerogen, the source of oil and gas deposits. Kerogen can be evaluated by organic geochemistry and organic penological methods, whose parameters are used to define organic fades for fine-grained, sedimentary rock sequences. Organic geochemistry uses Rock-Evalpyrolysis and elemental analysis to determine amounts of organic C, H, and Ï in kerogen to assess petroleum potential and origin. Organic petrologyuses reflected light microscopy to characterize dispersed organic matter in rocks, in terms of macérais and organic facies, which is then used to interpret the paleoenvironment and paleoecologyof organic-rich sedimentary rocks. This paper outlines the organic petrology of several hydrocarbon source rocks from western Canada, illustrating the success of this method in evaluating and understanding organic-rich rocks.